Case 3786: Helix dibothrion Bielz, 1860 (currently Perforatella dibothrion, Gastropoda, Stylommatophora, Hygromiidae): proposed conservation by suppression of the senior synonym Helix diodon Rossmässler, 1835 and proposed conservation of its prevailing spelling - Hausdorf, Bernhard (Bulletin of Zoological Nomenclature, 2019)
The purpose of this application, under Articles 23.9.3, 78.1 and 80.2 of the Code, is to suppress the senior synonym Helix diodon Rossmässler, 1835, in order to protect the name Helix dibothrion Bielz, 1860 (currently Perforatella dibothrion), which has been consistently in use for more than a century and to conserve the commonly used but incorrect spelling of the name.
Keywords: Nomenclature; taxonomy; Gastropoda; Stylommatophora; HYGROMIIDAE; Perforatella; Carpathian Mountains